Towards Environmentally Sustainable Development in Sub-Saharan Africa - World Bank (Washington, DC, 2012)
Environmental degradation primarily affects the poor, both in rural and urban areas. Reversing the downward spiral of this degradation is essential to any strategy for reducing poverty in Sub-Saharan Africa. This study outlines the World Bank's strategy for improving its assistance to SSA countries as they move toward environmentally sustainable development (ESD). It assesses the environmental situation and long-term trends in Africa, draws lessons from Bank experience, and proposes new directions. The study focuses on three questions: what are the key environmental issues and challenges in Sub-Saharan Africa? How has the World Bank responded to those challenges, and what are the lessons learned? And what should the World Bank do to help African countries make their development sustainable?